Nurturing innovations for early generation seed production - International Potato Center (2016)
National Agricultural Research Institutes and private sector partners in 11 countries are exploring innovations to reduce cost and increase multiplication rates of early generation seed. Astute monitoring of the seed production environment can lead to incremental changes to the range of factors which influence costs and growth conditions